Maintaining the Momentum While Addressing Service Quality and Equity : A Diagnostic of Water Supply, Sanitation, Hygiene, and Poverty in Ethiopia - World Bank (World Bank, Washington, DC, 2018)
This summary report presents the findings of the Ethiopia WASH Poverty Diagnostic (EWPD) study led by the World Bank`s Water and Poverty Global Practices. Though Ethiopia has made good progress in increasing access to water supply, sanitation, and hygiene (WASH) services in recent years, the quality of many services are below the standards set for meeting the Sustainable Development Goals (SDGs). The study review existing institutional structures and challenges that are inhibiting high-quality service delivery. The EWPD also reviews the quality and inequality in access to WASH service between those living in urban and rural areas, as well as different regions, areas of water insecurity and amongst the poorest households. EWPD also attempts to show the implications of poor access to WASH services on human development (health, nutrition, and education) and poverty reduction. The analysis aims to support the government and other stakeholders identify gaps in service delivery and answer questions on why these gaps exist. The report concludes by offering recommendations for moving Ethiopia`s WASH sector forward.